Effects of Cutting Size, Rooting Media and Planting Time on Rooting of Domat and Ayvalik Olive Olea europaea L. Cultivars in Shaded Polyethylene Tunnel Spt - Arzu Çetintaş Gerakakis; Mücahit Taha Özkaya (Journal of Agricultural Sciences)
Domat difficult to root and Ayvalık easy to root are important olive cultivars for green table olives and olive oil respectively in Turkey. This research was carried out to obtain ready to sale nursery plants of Domat and Ayvalık. It was achieved rooting their cuttings in different sizes and under different media and taken in different times of the crop year in Shaded Polyethylene Tunnels SPT . Cuttings were prepared in three sizes: 1, 2 and 3 nodes with two leaves. Rooting media was; I. Control Sand , II. Perlite: Peat: Sand: Silt 1:1:1:1 , III. Perlite: Peat: Sand: Silt 1:2:1:2 , IV. Perlite: Peat: Sand: Silt 1:1:2:2 , V. Perlite: Peat: Sand: Silt 0:0:1:1 and VI. Perlite: Peat: Sand: Silt 1:0:1:1 . Cuttings were kept in SPT for 60 days for rooting and then kept under shade for another 30 days. Vegetative growth characteristics were determined by studying percent survival rate, callus development and rooting. While, Ayvalık cuttings formed both callus and roots, Domat cuttings formed only callus. The highest callus formation 70% was observed on Ayvalık cuttings 1 node taken in May in 1:0:1:1 rooting media, but the highest rooting 40% was observed on cuttings of three nodes in the same date and media. In Domat, the highest callus was formed on cuttings 3 nodes in May in 1:2:1:2 media. The rooting was very low in Domat however, as it was for Ayvalık too. This was probably because rooting media did not form a suitable environment for adventitious root formation. Cuttings with 1, 2 and 3 nodes carrying 2 leaves differed in percent rooting with different treatments. All three sizes of cuttings can be used in propagation by rooting for the economical use of stock material